Influence of Intra-ductal Carcinoma on Clinical Outcomes in Men with Prostate Cancer: Systematic Review and Meta-analysis - Jatinder Kumar; Muhammad Umar Alam; Karthik Tanneru; Shiva Gautam; Daniel Norez; Charu Shastri; Joseph Costa; Mark Bandyk; Hariharan Palayapalayam Ganapathi; Shahriar Koochekpour; Sanjeev Shukla; KC Balaji (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
Purpose: To provide a comprehensive summary of published literature regarding influence of intraductal carcinoma of prostate (IDC-P) on clinical outcomes in men with Prostate Cancer (PC). Methods: We compared the following clinical endpoints in men with PC with or without IDC-P; Castration Resistant Free Survival (CFS) and Overall Survival (OS) for metastatic PC (Group 1), biochemical recurrence rate (BR) and/or cancer specific survival (CSS) in men undergoing radical prostatectomy (Group 2a) or radiotherapy (Group 2b). A meta-analysis was done by fixed effect model using 12 studies reporting Hazard Ratio (HR) and meeting the selection criteria.  Results: In Group 1 for men with IDC-P, the pooled HR for CFS and OS were 1.69 (CI, 1.30-2.21) and 2.00 (CI, 1.38-2.91), respectively. In group 2a BR and CSS were higher in men with IDC-P with HR 2.63 (CI, 1.99-3.49) and 2.87 (CI, 1.65-5.01) respectively. Similarly, presence of IDC-P in group 2b demonstrated a HR of 2.04 (CI, 1.10-3.78) for BR. Conclusions: Men with IDC-P demonstrated poorer clinical outcomes including higher rate of BR following radical prostatectomy, radiation therapy either in primary and salvage settings, shorter time to CFS and poorer OS in men with metastatic disease. Our analysis and review of the literature suggest that IDC-P could be used as a novel prognostic and predictive morphological biomarker to influence clinical management in men with PC including pelvic lymph node dissection, pelvic radiotherapy or genetic testing.